HIV molecular transmission networks among students in Guangxi: unraveling the dynamics of student-driven HIV epidemic - Xianwu Pang; Jie Ma; Qin He; Kailing Tang; Jinghua Huang; Ningye Fang; Haomin Xie; Guanghua Lan; Shujia Liang (Emerging Microbes and Infections)
In Guangxi, the number of newly diagnosed HIV-1 infections among students is continuously increasing, highlighting the need for a detailed understanding of local transmission dynamics, particularly focusing on key drivers of transmission. We recruited individuals newly diagnosed with HIV-1 in Nanning, Guangxi, and amplified and sequenced the HIV-1 pol gene to construct a molecular network. Bayesian phylogenetic analysis was utilized to identify migration events, and multivariable logistic regression was employed to analyze factors influencing clustering and high linkage. The predominant subtype among students was CRF07_BC (58.5%), followed by CRF01_AE (17.4%) and CRF55_01B (13.5%). Transmission network analysis identified a significant clustering rate of 64.3% among students, primarily within large clusters. The strongest transmission relationships were observed between students and MSM aged 25–39, as well as nonstudent youths. These migration events primarily occurred from MSM aged 25–39 to students and nonstudent youths for CRF01_AE, CRF07_BC, and CRF55_01B. Qingxiu was the main emigration region for for CRF01_AE, CRF07_BC, while Xixiangtang for CRF55_01B. Link with nonstudent youths (AOR = 5.11) and MSM aged 25–39 (AOR = 8.82) were significant factors contributing to the high linkage among students. Long-term infection was a key factor in super spreaders. These findings emphasize the critical role of MSM aged 25–39 in HIV-1 transmission among local youths, particularly regarding long-term infected individuals. The study advocates for targeted HIV-1 screening and intervention strategies for youths to strengthen early detection and treatment, thereby mitigating further transmission within this high-risk group.